The Implementation Of The Military Skills Development For Military Prisoners In Military Correctional Institutions - Arief Fahmi Lubis (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2024)
The execution of the rehabilitation of military prisoners is carried out through a communicative and accommodating approach, involving direct interaction between officers and military prisoners via counseling or interviews. This aims to listen, accept, discover, regulate emotions, strengthen spirituality, and resolve personal and official issues while fostering dedication, sincerity, responsibility, and loyalty within the Indonesian National Armed Forces environment. The objective of this study is to demonstrate the existing challenges in implementing military prisoner development that need to be addressed and overcome. In this study, the author applied qualitative research employing a descriptive approach to systematically, factually, and promptly gather data in line with the research’s context. The findings of this study demonstrated that the success of rehabilitating military prisoners in military correctional institutions is not solely within the responsibility of the Center for Military Correctional Institutions and the Military Correctional Institution itself. It is also affected by external factors, including the attention and moral support offered by the unit commander from the origin place of the military prisoners. This influence aims to facilitate military prisoners’ transformation into soldiers embodying Sapta Marga values, ensuring their readiness for forthcoming unit responsibilities.